2018
DOI: 10.1021/acsnano.8b01071
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Anchored Metal–Organic Frameworks as Versatile Resists for Gas-Assisted E-Beam Lithography: Fabrication of Sub-10 Nanometer Structures

Abstract: We demonstrate that surface-anchored metal-organic frameworks (SURMOFs) are extraordinary well-suited as resists for high-resolution focused electron beam induced processing (FEBIP) techniques. The combination of such powerful lithographic protocols with the huge versatility of MOF materials are investigated in respect to their potential in nanostructures fabrication. The applied FEBIP methods rely on the local decomposition of Fe(CO) and Co(CO)NO as precursors, either by the direct impact of the focused elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…The working stage has a travel range of 200 mm * 200 mm in the X-Y plane and 5 mm in the vertical direction with a resolution of 50 nm, which enables us to achieve a large exposure area over the substrate and a precise control of the focus. This lithography technique can generate features on the 2∼8 inch substrate and the maximum exposure area is 200 * 200 mm 2 . Fig.…”
Section: Dmd-based Maskless Lithography Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The working stage has a travel range of 200 mm * 200 mm in the X-Y plane and 5 mm in the vertical direction with a resolution of 50 nm, which enables us to achieve a large exposure area over the substrate and a precise control of the focus. This lithography technique can generate features on the 2∼8 inch substrate and the maximum exposure area is 200 * 200 mm 2 . Fig.…”
Section: Dmd-based Maskless Lithography Systemmentioning
confidence: 99%
“…The resin used in this fabrication process is photocurable resin, which can be identified from the relationship between the exposure dose and height, where the exposure threshold Eth and the contrast γ of the photoresist are 1.2 mJ/cm 2 and 0.2598, respectively, the maximum height of the development, H total , is 2.8 μm, and the required exposure dose is 61 mJ/cm 2 . Then, the exposure dose for the structure height can be calculated according to (1) and (2).…”
Section: Experimental Exploration and Improvementmentioning
confidence: 99%
“…On the one hand this is advantageous at the current status of the project, since deposits do not alter significantly during fabrication of further structures and several deposits can be analyzed in parallel after removal of the precursor gas. However, autocatalytic growth is an important mechanism towards clean deposits in FEBIP [1,15,100,101]. We propose that the current gas flow cell does not provide sufficiently clean conditions for proper autocatalytic growth and any catalytic effect is quenched by rapid contamination of deposited metal atoms.…”
Section: What We Have Already Learned About Fxbidmentioning
confidence: 96%
“…In an autocatalytic growth process, the initial deposits fabricated by either method grow in size as long as the precursor is supplied. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Important Surmof Topicsmentioning
confidence: 99%
“…Very recently, Drost et al demonstrated that SURMOFs can be loaded with metal–organic guest molecules and then used as resists for high‐resolution focused electron beam induced processing techniques, as shown in Figure B. Based on this technique, a deposit structure less than 8 nm has been achieved.…”
Section: Important Surmof Topicsmentioning
confidence: 99%